All Days 2008
DOI: 10.2523/iptc-12439-ms
|View full text |Cite
|
Sign up to set email alerts
|

Geology Drives Technology - Application of Coil Tubing Underbalanced Drilling in the Cooper Basin, Australia

Abstract: TX 75083-3836, U.S.A., fax +1-972-952-9435. AbstractRecord breaking oil prices and the forecasted upward pressure on gas prices form an exciting future for Australia's hydrocarbon industry. This commercial back-drop is creating a heightened interest in new technologies capable of improving recovery factors and accelerating production particularly in brownfield environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Obviously, the restricted pulling capacity, weight limitation, and inability to rotate the string or place drilling jars within the continuous string can often limit coiled tubing drilling and fishing capabilities in horizontal wells. However, several documented case studies (Solanet et al, 1999;Byrom, 1999;McCarty et al, 2002;Engel and Rae, 2002;Johnson, 2007;Telesford et al, 2008;Li et al, 2010) have shown that tremendous cost savings can be achieved by using coiled tubing for many drilling and completion applications.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, the restricted pulling capacity, weight limitation, and inability to rotate the string or place drilling jars within the continuous string can often limit coiled tubing drilling and fishing capabilities in horizontal wells. However, several documented case studies (Solanet et al, 1999;Byrom, 1999;McCarty et al, 2002;Engel and Rae, 2002;Johnson, 2007;Telesford et al, 2008;Li et al, 2010) have shown that tremendous cost savings can be achieved by using coiled tubing for many drilling and completion applications.…”
Section: Introductionmentioning
confidence: 99%